The labour of leisure: the work of square dance calling. Issue 4 (1st October 2016) - Schneider, Barbara; McCoy, Liza
ABSTRACT: Attention is increasingly being paid to the work involved in the production of leisure activities. In this article we offer an ethnographic description of the work of square dance calling and its role in the square dance community. Square dance is a form of social dance carried out by groups of four pairs of dancers arranged in a square, moving in response to on-the-spot instructions of a square dance caller. Callers' labour is at the centre of the square dance community. Calling on concepts of immaterial labour, affective labour, and virtuosity, we describe the mostly hidden work of the square dance caller, the goal of which is to produce a fun dance evening for participants. The multi-faceted labour of being a caller includes being a singer, an entertainer, an expert in calling, a teacher, a sound equipment expert, a business person, and an emotional worker instrumental in producing other people's pleasure in what is for them a leisure activity and thereby contributing to maintaining the square dance community.